2023
DOI: 10.3390/fishes8020095
|View full text |Cite
|
Sign up to set email alerts
|

Otolith Morphometric and Shape Distinction of Three Redfin Species under the Genus Decapterus (Teleostei: Carangidae) from Sulu Sea, Philippines

Abstract: Otoliths are paired calcified structures in the inner ear of teleosts that function in hearing and balance. In this study, the use of otolith morphometrics and shape analysis were explored to delineate the redfin species under the genus Decapterus from the Sulu Sea, Philippines, namely, Decapterus kurroides, D. smithvanizi, and D. tabl. Results showed that the mean otolith shapes are unique within species (p < 0.001). The otolith size-related (OW—otolith weight, OL—otolith length, OH—otolith height, OA—otol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…From the analysis in the paper, the differentiation results are similar to other previously published results for different species of one same genus [27,91,[99][100][101]. Some studies have been carried out using otolith shape analysis in tunas and small tunas, mainly for stock delimitation [29][30][31].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…From the analysis in the paper, the differentiation results are similar to other previously published results for different species of one same genus [27,91,[99][100][101]. Some studies have been carried out using otolith shape analysis in tunas and small tunas, mainly for stock delimitation [29][30][31].…”
Section: Discussionsupporting
confidence: 85%
“…The high differentiation and classification rates observed for our research-collected otoliths indicate that, as previously confirmed by genetic analyses, it follows that there are clear otolith shape differences between the Northeast Temperate Atlantic together with the Mediterranean Sea and Eastern Tropical Atlantic areas with a high degree of confidence. A pattern that is repeated in this type of study in the differentiation of species from shape otoliths, which is also fulfilled in our work, is that at least three otolith morphological descriptors analyzed show significant variations between the groups of individuals analyzed and 25% of the otolith outlines present great divergences [85][86][87][88][89][90][91]. Perhaps these are results to consider when carrying out an analysis of this type for the differentiation between species.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, in some other population studies, the overall discrimination success rate obtained by using elliptic Fourier coefficients exceeded 90.0% [40,41]. Morales et al conducted research on the otolith morphometric and shape distinction of three redfin species under the genus Decapterus (Teleostei: Carangidae); their results showed that the otolith shape analysis was effective in separating the redfin species of Decapterus from the Sulu Sea and identifying regions of marked differences in the otolith outline [42]. This research is similar.…”
Section: Discussionmentioning
confidence: 99%